Immunological response of resistant and susceptible Plutella xylostella (Lepidoptera: Plutellidae) to Bacillus thuringiensis - DA SOLIDADE-RIBEIRO, LÍLIAN MARIA; WANDERLEY-TEIXEIRA, VALÉRIA; DA CUNHA, FRANKLIN MAGLIANO; COELHO-TEIXEIRA, ÁLVARO AGUIAR; ABREU DE SIQUEIRA, HERBERT ÁLVARO (Revista Colombiana de Entomología, 2012)
Despite the proven efficiency of Bacillus thuringiensis (Bt) to insects, a number of resistance cases have been reported throughout the world particularly for Plutella xylostella (Lepidoptera: Plutellidae) populations. Although the mechanism of resistance to Bt toxins due to altered receptors appears to be common among Lepidoptera, few studies have evaluated the immune response to Bt toxins in resistant insects. Thus, this study aimed to compare the total and differential counts of hemocytes as well as the nitric oxide levels in resistant and susceptible populations of P. xylostella to Bt after exposure to dipel®PM (Btk) and xentari®WdG (Bta) commercial formulations. Susceptible and resistant insects were exposed to their corresponding LC50 of dipel®PM or xentari obtained through dose-response curves. Hemolymph samples were collected at 1, 6, and 12 h after treatment for total and differential hemocyte counts and quantification of nitric oxide levels. Dipel®PM caused a significant reduction in the total number of hemocytes in the larvae of both populations, while xentari®WdG affected only the proportion of types of hemocytes. Both formulations interfered with the nitric oxide levels, although no difference was observed between both populations.